Prevalence of meconium-stained amniotic fluid and factors associated with emergency cesarean section: multicenter cross-sectional study in south central Ethiopia - Tantu, Temesgen; Melkamu, Biruk; Gunta, Muluken; Tantu, Tayech; Aregawi, Yohanna; Gashaw, Dereje (Frontiers in Global Women's Health, 2024)
BackgroundMeconium is thick black-green fetal intestinal content starting from the early first trimester of gestation. Unfortunately, if it is released into the amniotic cavity due to any cause, it can be associated with neonatal mortality and morbidity.ObjectiveTo identify the factors associated with meconium-stained amniotic fluid among mothers undergoing emergency cesarean section in specialized hospitals cross-sectional study in south central Ethiopia from August 1, 2022, to 30, October 2022MethodInstitution based multicenter cross-sectional study was done prospectively through meticulous chart review and interview on 875 mothers who gave birth with emergency cesarean section. Data were entered using Epi data 7 and analyzed with SPSS 26. The association between independent variables and meconium-stained amniotic fluid was estimated using an odds ratio with 95% confidence intervals. The statistical significance of the association was declared at P-value < 0.05ResultThe prevalence of meconium-stained amniotic fluid is 31.4%. Gravidity (AOR 3.643; 95% CI:1.215,10.921), time interval between decision to delivery (AOR 1.361; 95% CI: 0.424,4.365),eclampsia(AOR 8.022; 95% CI: 1.634,39.372), time taken from referring institution to managing institution (AOR 15.258; 95% CI: 1.591,146.328), obstructed labor (AOR 24.614; 95% CI: 6.073,99.766), cephalopelvic disproportion (AOR 2.640; 95% CI:1.002,6.950), fetal heart beat abnormality (fetal bradycardia AOR 2.068; 95%CI 0.997,4.292) (fetal tachycardia AOR 3.513; 95% CI:1.633,7.556) duration of labor(AOR 5.44; 95% CI: 1.355,9.782) and referral from health center(AOR 5.41; 95% CI: 2.053,14.272) are associated with MSAF whereas obstetric complications(AOR 6.820; 95% CI: 2.870,16.202), cesarean section scar (AOR 3.010; 95% CI: 1.344,6.740) are negatively associated.ConclusionPrevalence of meconium-stained amniotic fluid is relatively high for which intrapartum, obstetric and institution related factors are incriminated. Therefore, an improvement in the quality of antenatal and intrapartum care is strongly recommended; professional development at the health center, building the infrastructure, and strengthening the referral system is also suggested.